Digital idiocy in higher education or political participation by other means? - Hansen, Stig Børsen (Tidsskriftet Læring og Medier (LOM), 2022)
This paper proposes a set of conditions for political participation. An understanding of the conditions for political participation is required for studying the extent to which digitizing higher education is detrimental to civic virtues, as it has been widely suggested. On the background of illustrative examples of on-campus political action, the paper explicates three preconditions of civic virtue: Firstly, an architectural aspect that can bar or allow for political action, through sit-ins, barricades and the like. Secondly, a virtue-forming aspect, where forms of collective action can help foster virtues by encouraging or sanctioning certain kinds of action. Thirdly, an informational aspect, where the structure of brick-and-mortar campuses can shape and strengthen politically significant informational structures, allowing for both common knowledge and public signals (open spaces) and “closed curtains” enclave deliberations. In contrast with a range of recent attempts at resisting a decline narrative by suggesting a change in the nature of political participation, the paper concludes by using the three aspects to point to possibilities of identifying the same aspects of civic virtue online as can be found in a physical, campus setting.